Programa de habilidades sociais na escola : uma forma de combate ao preconceito contra a diversidade sexual - Sousa, Kelyane Oliveira de (2017)
The effectiveness of a social skills program in reducing prejudice against sexual and gender diversity in adolescents is analyzed in this study. Twenty-two adolescents between 14 and 17 years old participated in the study, elementary school students from a public school located in Aracaju, capital of Sergipe. A quasi-experimental design of a discontinuous time series with pre-test and post-test was used. In the pre-test the levels of social skills and of prejudice against sexual and gender diversity of the investigated adolescents were verified. Subsequently, the experimental treatment was carried out through social skills training aimed at questions about sexual diversity and, after a week of its closure, the post-test was carried out, in which the levels of social skills and prejudice against Sexual and gender diversity were again checked. The instruments used in the pre and post-test were: Social Skills Inventory for Adolescents and the Sexual and Gender Diversity Prejudice Scale. The intervention had a total of 10 weekly sessions, each of 50 minutes, with a psychoeducational and cognitive-behavioral approach through strategically delineated techniques according to the general objective of the study. The results of the pre-test demonstrated that the youth had a low performance in the general frequency of social skills, as well as in the specific skills related to empathy, self-control, civility, assertiveness, affective approach, social skills and moderate level of prejudice against Sexual and gender diversity. After the intervention, the comparative data between the pre and post-test showed a significant reduction in the level of prejudice of the adolescents and a significant increase in the frequency of emission in three of the six subclasses of social skills, which were: assertiveness, affective approach and social resourcefulness.